Pengaruh Penambahan Sari Kedelai terhadap Karakteristik Mi Tofu Shirataki Kering Berbasis Tepung Porang Glukomanan - Maulani, Siti Patimah Zahro; Trianawati, Mrr Lukie; Sarifudin, Achmat (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Dry noodles are one of the fast foods that people like and are generally made from wheat flour. Rising wheat exports could threaten Indonesia's food security. Porang contains glucomannan and can be used as a substitute for flour. This study used the addition of soybean juice to add protein to Shirataki noodles. The purpose of the study was to determine the effect of the addition of soybean juice on the texture characteristics and protein content of Shirataki tofu noodles. This study used 3 treatments, namely the addition of soybean juice (2.5%, 5%, and 7.5%). Based on the results of the study, the addition of soybean juice had a significant effect on the analysis of ash content, protein content, hardness, color and sensory. Meanwhile, the results of the study did not have a significant effect on the analysis of morphology, water content, water activity, and elongation. The results of research on physical analysis showed the best sample concentration of 2.5%, in chemical analysis the best concentration of 2.5% except for the best sample protein analysis of 7.5%, and in sensory analysis of the sample preferred concentration of 5%.